Industrial Minerals - Effect of Ultrasonic Energy of Chrysotile Asbestos - E. Martinez (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1963)
The effect of ultrasonic energy transmitted through a liquid on chrysotile asbestos was investigated. Ultrasonic energy was effective in fiberization of chrysotile crudes as well as standard grades of milled asbestos fibers. Treated samples of several grades of milled fibers had increased wet bulk volumes and decreased settling and filtration rates compared to untreated fibers. Ultrasonics may be a method for fiberization of chrysotile without decreasing length or use of chemical additives that alter surface properties. Cavitation of the liquid on the surface of fiber bundles is believed to be the cause of the fiberization. It was found that ultrasonic energy greatly increased the rate of precipitation of latex on asbestos. When chrysotile asbestos fibers require additional opening or fiberization, the usual method employed is some type of high speed impact or grinding to open the fibers and produce a larger surface area. These methods always cause some degradation in length due to breaking of fibers. In addition, the efficiency of mechanical methods decreases as the diameter of fiber bundles decreases. Chemical methods have been proposed and it is claimed that fiberization down to individual fibers of 200-300 A diam is possible with some wetting agents. However, large amounts of reagent are required, approximately EDWARD MARTINEZ is with Central Research Laboratories, American Smelting and Refining Co., South Plain-field, N.J. TP 63H226. Manuscript, Aug. 12, 1963. Discussion of this paper, submitted in duplicate prior to Mar. 15, 1964, will appear in SME Transactions, September 1964, and AIME Transactions, 1964, vol. 229. 50 pct of the weight of fiber treated, and some of the wetting agent remains on the surface of the chrysotile and cannot be removed by any solvent which does not destroy the asbestos.' This investigation was directed at determining whether ultrasonic energy transmitted through a liquid would be effective in fiberizing chrysotile asbestos. Samples of asbestos crudes and commercially milled fibers were treated; settling and filtration rates of treated and untreated milled fibers were obtained. EQUIPMENT A Westinghouse Corp. ultrasonic cleaning system WEHH was used in this investigation. See Table I for a breakdown of this ultrasonic unit. RESULTS AND DISCUSSION Fiberization of Chrysotile Crudes: Samples of chrysotile crudes were pulled apart with tweezers so that coarse bundles of fiber approximately 1/16 in. in diam were obtained. The bundles were put into a bottle with 200 ml of methanol and the mixture placed into the ultrasonic tank for 30 min at a power output of 1200 w. The test was repeated using water instead of methanol. During the irradiation it was noted that the surfaces of the bundles were being fiberized. The liquid eventually became cloudy with dispersed solids. Fig. 1 is an electron micrograph of the fibers, some reduced to unit dimensions, and a fine material released by the ultrasonic energy. The platy particles in Fig. 1 were identified by electron diffraction and differential thermal analysis as brucite, Mg(OH)2, which must have been intergrown in the chrysotile crudes. Electron micrographs of bulk specimens of chrysotile have shown a fine material filling the interstices between tubular fibers.2,3 Electron diffraction patterns of the fine material collected after ultrasonic treatment indicate that it is amorphous. After decanting the solution, bundles of chrysotile remained somewhat decreased in diameter. Continuing the ultrasonic irradiation of the remaining material resulted in additional fiberization. The opening of the fibers occurred in both methanol and water. Cavitation of the liquid by the ultrasonic energy is undoubtedly responsible for the fiberization. When sound waves are transmitted through a liquid at a